Hubungan pengetahuan ibu hamil tentang antenatal care terhadap perilaku kunjungan kehamilan - Febyanti, Niken Kurnia; Susilawati, Dwi (Jurusan Keperawatan FIKES UNSOED, 2012)
Antenatal care (ANC) is a regular maternal and fetal check followed by an attempt of correction of complication found. In pregnancy, pregnant women should consult their pregnancy as many as 12 times. The aim of this research was to determine the correlation of 3th trimester pregnant women’s knowledge about the importance of antenatal care towards visiting behaviors. This research was a quantitative research with questionnaire as the instrument. The study population was all 3th trimester pregnant women who checked their pregnancy at the public health center of Banyumanik subdistrict, Semarang city, with total sample of 64 respondents in accidental sampling. The result of study showed p value < 0.05. It was concluded that there was a correlation between pregnant woman’s knowledge towards visiting behaviors. Pregnant women are suggested to improve their awareness of the importance of antenatal care.